First Riding Lessons - Sandy, Ransford (New York kingfisher, 2004)
Summery: Presents detailed information on beginning various types of ponies and horses and Kinds of equipment used
Learn to walk, trot, canter, and jump
12
Keywords: Animal welfare; Animals -- Training; Horsemanship; Horses -- Training